2017
DOI: 10.1155/2017/9042851
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis: A Fundamental Process in Immunity

Abstract: One hundred years have passed since the death of Élie Metchnikoff (1845–1916). He was the first to observe the uptake of particles by cells and realized the importance of this process for the host response to injury and infection. He also was a strong advocate of the role of phagocytosis in cellular immunity, and with this he gave us the basis for our modern understanding of inflammation and the innate and acquired immune responses. Phagocytosis is an elegant but complex process for the ingestion and eliminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
312
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 402 publications
(341 citation statements)
references
References 170 publications
(207 reference statements)
1
312
0
1
Order By: Relevance
“…Neutrophils are the first line of defense against infections because they are the first leukocytes to arrive at the affected tissue . In there, neutrophils display several antimicrobial mechanisms, including phagocytosis, respiratory burst, degranulation, and the formation of NET . In the case of amoeba infection, phagocytosis is not suitable because trophozoites are much larger than neutrophils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutrophils are the first line of defense against infections because they are the first leukocytes to arrive at the affected tissue . In there, neutrophils display several antimicrobial mechanisms, including phagocytosis, respiratory burst, degranulation, and the formation of NET . In the case of amoeba infection, phagocytosis is not suitable because trophozoites are much larger than neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Upon recognition of trophozoites, only the neutrophils in direct contact with the parasite release DNA fibers that can completely cover and immobilize the amoeba. Because neutrophils cannot phagocytize large cells, they release NET in those cases to prevent the pathogen from escaping. Thus, instead of the amoeba inducing neutrophil apoptosis, it is the neutrophil attacking the trophozoite by undergoing NETosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low expression of CD16 was also observed in human BMMC-differentiated macrophages (Koller et al, 1996;Rozner et al, 2009), suggesting that this is a common feature of bone marroworiginated macrophages across these primate species. Additionally, bone marrow-differentiated cynomolgus-monkey macrophages express receptors that are critical for macrophage function, such as those responsible for pathogen phagocytosis (the mannose receptor CD206 and the high-affinity scavenger receptor CD163) and receptors delivering costimulatory signals to T cells (CD80 and CD86) (Odobasic, Leech, Xue, & Holdsworth, 2008;Rosales & Uribe-Querol, 2017).…”
Section: Background Informationmentioning
confidence: 99%
“…Neutrophil phagocytosis is a complex process that can occur via (a cross-talk of) various receptors, including pathogen-associated molecular pattern (PAMP) receptors, Fcγ receptors (FcγRs) and complement receptors (CRs). 51 Since FES was previously reported to regulate cell surface receptors, including TLR4 in macrophages 52 and FcεRI in mast cells 11,19 , we wondered whether FES might be involved in neutrophil phagocytosis. First, we confirmed that treatment of live neutrophils with a low concentration of WEL028 (100 nM, 1 h) resulted in complete and selective inhibition of FES in the mutant cells ( Figure 6A-B).…”
Section: Step 3 -Crispr/cas9 Gene Editing Enables Visualization Of Enmentioning
confidence: 99%